A text book of electrical technology; alternating and direct current engineering in rationalized M. K. S. A. system of units for the examinations of B. Sc. - Theraja, B. L. (New Delhi, S. Chand Publications, 2000)
Use as a text book.
0
0
0
0
0
0
Keywords: Electrical engineering